Restitution for Victims in Juvenile Criminal Justice: Legal Mechanisms, Challenges, and the Path to Justice in Indonesia - Ni Kadek Susantiani; Nur Basuki Minarno (Vifada Assumption Journal of Law, 2026)
Purpose: This study critically examines the normative framework and practical implementation of restitution for victims within Indonesia’s juvenile criminal justice system. It aims to assess whether restitution under UU SPPA effectively reflects restorative justice principles and supports meaningful victim recovery. Research Design and Methodology: The research employs a doctrinal-normative legal method using statutory, conceptual, case, and comparative approaches. Data were collected from legislation, judicial decisions, scholarly literature, and international legal instruments. A comparative analysis was conducted with restitution frameworks in the Philippines and Thailand to identify potential reform models relevant to Indonesia. Findings and Discussion: The study finds that restitution remains narrowly interpreted as financial compensation, limiting recognition of psychological, symbolic, and service-based forms of reparation. Its implementation is further constrained by procedural complexity, fragmented institutional coordination, and limited judicial discretion. Comparative findings reveal that more flexible and community-based restitution mechanisms in the Philippines and Thailand. Implications: The findings suggest the need to broaden the legal definition of restitution, simplify procedures, strengthen institutional support, and introduce alternative forms of victim-centered reparation. These reforms would enhance restorative justice implementation, align Indonesian juvenile justice with international child rights, and provide a stronger foundation for future policy and empirical research.